Surface topographical studies of glass fiber reinforced epoxy-ZnO nanocomposites. (25th November 2019) - Thipperudrappa, Sridhar; Kini, Achutha Ullal; Hiremath, Anupama; Kumar, Karani Dileep
Abstract: The objective of present research work is to investigate the surface morphology and surface microhardness of unidirectional E-glass fiber epoxy composites filled with varying amount of ZnO nanofiller content such as 1, 2, 3, 4 and 5 wt% respectively. ZnO nanofiller was added to the epoxy resin matrix in varying amount (wt%) using mechanical stirrer and followed by ultrasonication process. The laminate composites were fabricated using a compression molding press technique. Further, laminate composites were subjected to individual characterization and testing according to ASTM standards. The crystalline nature of ZnO nanofiller was studied using x-ray diffraction analysis (XRD) and surface morphology of ZnO nanofiller on the resin surface was examined by using a scanning electron microscope (SEM). The experimental test results revealed that addition of nanofiller content by 1, 2 and 3 wt% resulted in a gradual reduction of void fraction and thereafter increase in void fraction was observed with 4 and 5 wt% of ZnO loading. The surface microhardness results indicated a linear increment with increase in ZnO nanofiller loading from 1 to 5 wt%. Further, surface topography was studied with the help of atomic force microscopy (AFM), to obtain the surface roughness values. The surface roughness values increased with increase in ZnO wt% within the epoxy resin matrix. The results of the surface analysis of the fabricated composites indicate that at higher loading of ZnO nanofiller, there is formation of clusters and agglomerates of the nanofiller which reduces the nano-scale effects of the filler and nanofillers tend to behave as micro-fillers.